Radiation Boost After Adjuvant Whole Breast Radiotherapy: Does Evidence Support Practice for Close Margin and Altered Fractionation? - Gulstene, Stephanie; Raziee, Hamid (Frontiers in Oncology, 2020)
Adding boost to whole breast radiation following breast conserving surgery can help improve local control. However, it increases the total cost of treatment and may worsen cosmetic outcomes. Therefore, it is reserved for patients whose potential benefit outweighs the risks; however, current evidence is insufficient to support comprehensive and consistent guidance on how to identify these patients, leading to a potential for significant variations in practice. The use of boost in the setting of close margins and hypofractionated radiotherapy represents two important areas where consensus guidelines, patterns of practice, and current evidence do not seem to converge. Close margins were previously routinely re-excised, but this is no longer felt to be necessary. Because of this recent practice change, good long-term data on the local recurrence risk of close margins with or without boost is lacking. Consequently, the recommendations around the management of close margins are somewhat vague. As for hypofractionation, although there is guidance recommending that the decision to add boost be independent from the whole-breast fractionation schedule, it appears that patterns of practice may show underutilization of boost when hypofractionation is used. The use of boost in these two common clinical scenarios represent important areas of future study for the optimization of adjuvant breast radiation.